Effects of milk, milk replacer, and milk replacer plus ethoxyquin on the growth performance, weaning stress, and the fecal microbiota of Holstein dairy calves - Wei, Xiaoshi; Zou, Jifu; Zhang, Yiwei; Yang, Jinyong; Wang, Junhong; Wang, Yanming; Wang, Chong (Frontiers in Microbiology, 2023)
The early growth and health status of calves have a significant effect on milk production during the first lactation. Using appropriate milk replacer is meeting the long-term targets of dairy farmers. This study aimed to elucidate the effects of milk, milk replacer, and milk replacer plus ethoxyquin on growth performance, antioxidant status, immune function, and gut microbiota in Holstein dairy calves. A total of 36 neonatal dairy calves were randomly divided into 3 groups, fed milk, milk replacer, and milk replacer plus ethoxyquin. The ethoxyquin was supplemented beginning at days 35. The calves were weaned at days 45, and the experiment was conducted until days 49. The blood and fecal samples were collected at the end of animal experiment. Results showed that milk replacer induced poor growth performance (body weight and average daily gain). Milk replacer plus ethoxyquin benefited the growth, enhanced the starter intake and blood antioxidative ability, and elevated the concentration of fecal valeratic acid. Moreover, fecal fermentation and 16S rRNA analyses showed that milk replacer plus ethoxyquin altered microbial composition (reducing Alistipes and Ruminococcaceae, and increasing Bacteroides and Alloprevotella). Pearson’s correlation assays showed alterations in fecal microbiota were strongly correlated to average daily gain and antioxidative ability. The results suggested the potential of milk replacer plus ethoxyquin in modulating growth of dairy calves and enhancing ability to defense stress.